Effect of Feeding Hay Treated with Urea on The Reproductive Efficiency of Local Female Goats in The Northern Part of The Governorate - Nasser, Sakain Aidan; Mohammed Mousa Ouda (Universitas Muhammadiyah Sidoarjo, 2025)
Nutritional deficiencies, particularly protein shortage, negatively affect reproductive performance and metabolic functions in ruminants. Urea-treated roughages are increasingly used as an economical non-protein nitrogen source to enhance feed quality and improve reproductive efficiency in goats. However, evidence on their physiological and reproductive effects in local goat breeds remains limited. Few studies have systematically evaluated how different urea concentrations in treated barley straw influence reproductive efficiency, metabolic biomarkers, hormone profiles, and offspring performance in female local goats. This study aimed to determine the effects of feeding barley straw treated with 1% and 3% urea on feed intake, reproductive efficiency, blood biochemical parameters, reproductive hormones, and offspring growth in local female goats. Twenty-one goats were divided into three equal groups (control, 1% urea, 3% urea). The 3% urea group showed the highest roughage intake and final body weight (55.28 kg). Fertility and reproductive efficiency varied among groups, with the 3% group achieving notable performance. Blood urea concentrations significantly increased in urea-treated groups (P < 0.01), while total protein, albumin, globulin, creatinine, estrogen, LH, and progesterone showed no significant differences (P > 0.05). AST increased and ALT decreased non-significantly. FSH levels increased significantly in urea-treated groups (P < 0.05). Offspring in the 3% urea group recorded the highest birth and weaning weights. This study provides one of the first detailed physiological and reproductive assessments of urea-treated barley straw in local Iraqi goats. Urea treatment at 1–3% can enhance feed quality and support reproductive and growth performance without adverse metabolic effects, offering a cost-effective feeding strategy for local goat production. Highlights Feeding goats with 3% urea-treated barley straw improved roughage intake, final body weight, and offspring birth and weaning weights. Urea treatment significantly increased blood urea and FSH levels, while other biochemical and hormonal parameters remained within normal ranges. Urea-treated straw enhanced reproductive efficiency without causing adverse metabolic effects, supporting its use as a cost-effective feeding strategy.